The Short Witticisms Of The Classic Bulgarian On Facebook – Establishing The Genre And Reviewing Its Linguistic Features - Dichev, Bogdan (Media and Language, 2024)
The text examines the emergence of a type of humorous genre in Facebook, unknown until a few years ago, shaping new speech constructions in the virtual medium, a new manner of verbal expression. In many cases, these verbal forms are part of memes with a particular, almost normative textual component. It is this normativity of it that conditions verbal opuses as a new media and folk genre. The short prose fragments are conveniently called “ganiographs” because they ridicule the new incarnations of the contemporary Bai Ganyo, referred to by the members of the humor and entertainment groups as the “classic Bulgarian” or “the Classic.”The original authorship of these witticisms subsequently becomes difficult to trace in the many republications, until it is eventually lost and so many of them become a kind of virtual folklore – they become folklorized. Their emergence is seen in two ways – as text within the meme and as text detached from the meme’s dissolution. Because of their field of emergence and development, ganiographs belong simultaneously to contemporary folkloristics and to media language. Although they are originally short forms, they can also evolve to more voluminous narrative wholes, almost to the level of the short story.The cultural and semantic shape of the etudes for the classical Bulgarian are examined, as well as their narrative projections, but the bulk of the development explores the linguistic aspects of these newly emerging verbal constructions – their grammatical, lexical and stylistic aspects are analysed in comparative detail. At the end, the relation of the verbal genre to the image is presented, its possible liberation from its syncretic inseparability from the visual is discussed, and extensive appendices are added.
Keywords: Humor on Facebook; the meme as synthesis and decay; the gag as a new folk genre; cultural and narrative particularities; analysis of linguistic aspects